Analisis Kesehatan Sektor Bank Digital yang Terdaftar di BEI dengan Pendekatan Risk Based Bank Rating pada Periode 2022-2024 - Iswardhani, Indri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the health of the digital banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024 using the Risk-Based Bank Rating (RGEC) approach, which involves four main aspects: risk profile, good corporate governance, earnings, and capital. The research method used is descriptive quantitative analysis with secondary data. The sampling method was purposive sampling, which includes four digital banks listed on the IDX: ARTO (Bank Jago Tbk), BBHI (Bank Harda Internasional Tbk), BBYB (Bank Neo Commerce Tbk), and AMAR (Bank Amar Indonesia Tbk). The results show that based on the composite value calculations, these digital banks have shown significant improvement, moving from a composite rating of 3 (PK-3) with a